Age Related Histomorphological Study on Connecting Rete Tubules in Ovarian Rete System of Buffalo - Kumari, Nawesha (Indian Journal of Veterinary Anatomy, 2018)
The present study showed that the connecting rete was present between the intraovaraian and extraovarian rete tubules. At early foetal age, these tubules appeared as a discrete structure lined by basement membrane with abundance of connective tissue. At later stages of prenatal life, which were well developed and had two components i.e darkly stained mesovarian connecting rete lined by pseudostratified columnar type cells and had a larger lumen. The second type were lightly stained ovarian proper connecting rete, which were also lined by pseudostratified columnar type with a distinct basement membrane underneath, but had small lumen. At this stage, the amount of connective tissue fibres was more and leading to separation of individual tubules. During prepubertal groups, mesovarian connecting rete tubules occupied the larger area of the ovarian medulla and had larger diameter and with or without luminal contents. In  pubertal animals, decreased number and size of connecting rete with an increase in the connective tissue separating the tubular components. Present observations indicated that the connecting rete were well developed during late prenatal and prepubertal animals which showed degeneration with age ofanimals may in turn be correlated with the reproductive activity of animal.